Implementation of active magnetic control system for piston centering in labyrinth piston compressor. (October 2018) - Xie, Jing; Zeng, Xiangjun; Zhang, Meimei; Cheng, Junming; Wang, Hang
Abstract: This paper introduces a kind of active magnetic control system (AMCS) to solve the problem of the eccentric running of the piston in labyrinth piston compressor. Besides, a new control strategy based on three closed-loops of current, speed and displacement is applied to the control system. Firstly, the structure of the labyrinth piston compressor and the typical force condition to the piston are given. According to this, the AMCS that mainly contains the electromagnetic guiding sleeve, the displacement sensor, the piston rod and the control circuit is designed. And the model of the AMCS is built. Hereinto, the model of the electromagnetic coil in the guiding sleeve is nonlinear and a linearization method is proposed. Secondly, the three closed-loops control strategy is modeled and the regulators are designed. And the speed closed-loop is built on a new speed observation method of the least square linear fitting using the displacement data. Finally, simulation and experiments are done to verify the feasibility of the control system. The experimental results are in accordance with the simulated. It shows that the system can implement the precise centering of the piston. And the controller presents good robustness and high control precision.